The Effectiveness of Pillar One as a global solution to increase tax revenues for the UK and Africa - Govan, Hemletta (Department of Finance and Tax, 2024)
Digitalisation of economic activities has become a reality in todays ‘world economy'. The proliferation of technology and e-commerce may result in permanent establishments and corporate income taxes becoming outdated in the future. On 13 October 2021,137 countries of the 141 members of the OECD Inclusive Framework (IF) on Base Erosion and Profit Shifting committed to fundamental changes to the international corporate tax system. The 137 countries include the G7 members (Canada, France, Germany, Italy, Japan, United Kingdom, United States) and G20 members comprising an international forum for the governments and central bank governors and includes in addition Argentina, Australia, Brazil, China, EU, India, Indonesia, Mexico, Russia, Saudi Arabia, South Africa, South Korea and Turkey. It also includes developing countries such as Ghana, Tunisia, Algeria, Tanzania, Ethiopia. Countries such as Kenya, Nigeria, Shri Lanka and Pakistan did not sign on to the consensus. The IF issued a Two-Pillar Solution, comprising of Pillar One and Pillar Two to achieve a fairer distribution of profits and taxing rights among countries with respect to the largest MNEs. The main aim of the Pillar One solution is to create a single set of consensus-based international tax rules to address the tax challenges raised by digitalisation. Pillar One proposes re-allocating taxing rights of the largest and most profitable MNEs business activities and earned profits from their home countries to the markets, regardless of their physical presence. The proposal also aims to ensure that MNEs pay a fair share of tax in the countries in which they operate, to improve certainty, streamline the tax administration mechanisms, and to achieve a balance of the IF objectives that will result in the removal of unilateral measures. The OECD predicts that Pillar One will lead to an increase of approximately USD 125 billion annually to market jurisdictions and claims that developing countries will gain more revenue than developed countries as a share of CIT. Developed and developing countries rely on different composition of tax revenues with developed countries constituting a greater proportion of personal income tax and developing countries relying on corporate income taxes. Countries such as the United Kingdom(UK) started advocating the Digital Services Taxes(DST) at an early stage and enacted the DST from 1 April 2020 followed by the African Trade and Tax Administration publishing a draft guideline for DST legislation for African countries. This dissertation aims to understand how Pillar One would significantly increase revenue for the UK and for African countries and will question if Pillar One will provide an effective source of revenue in contrast to the DST legislated by the UK and the ATAF proposed DST for African countries. This dissertation starts by examining and understanding the evolution of Pillar One and the solutions proposed in the context of its IF and International tax rules and outlines the effectiveness and challenges of the solution. The understanding gained from this background was applied by evaluating and analysing the comparison of the Pillar One solution to the DST enacted by the UK, and to form a view by comparing the outcome of the UK position to the ATAF DST proposal to address the two subsidiary questions: Firstly, would the UK derive significant revenue by shifting from its current DST legislation to Pillar One? Secondly, would the 54 African countries be in a better position if it adopts the ATAF DST proposal as opposed to Pillar One? It was concluded that the UK yielded an overall net revenue loss when compared to the UK DST however the loss is relatively small when compared to the size of the economy. Considering the outcome of the evaluation, Pillar One may be the preferred solution for the UK. In reference to the second question, it is unlikely that the Pillar One solution will address the needs of the 54 African countries. It is also uncertain if the proposed ATAF DST with a recommended rate of between 1% and 2% is sufficient to mitigate the net revenue effect of Pillar One Amount A for most of the 54 African countries. A minimum DST rate at 3% or greater may exceed or raise as much revenue as Pillar One for most of the 54 African countries.